Interpretasi Hadis Larangan Melukis Prespektif Hermeneutika (Fazlur Rahman) - M. Alvin Setia Dharmawan; Fauzan Shodiqi; Kholila Mukaromah; Mohamad Ma'mun; Moh Shofiyul Huda MF (Canonia Religia, 2024)
Beauty is a quality greatly appreciated for its ability to soothe the heart and delight the eye. In art, beauty manifests through the cultural and spiritual expression of humanity. Visual arts, such as painting and photography, serve not only as adornments but also as mediums for conveying messages and emotions, linking personal expression with collective experiences. However, a hadith of the Prophet Muhammad SAW suggests that Islam does not sanction painting, stating that those who engage in it will face severe punishment in the afterlife. This necessitates a detailed and nuanced interpretative study of the hadith. This research adopts a thematic approach to analyse the hadith by reviewing its texts and related literature. Contextualisation is achieved by examining the historical context of the hadith and applying a hermeneutic method from Fazlur Rahman’s perspective, specifically through the concept of double movement. This method aims to clarify the context and purpose behind the prohibition of painting. The study explores how the hadith’s interpretation can be adjusted to fit modern social contexts and address potential misconceptions in contemporary art practices. The findings indicate that the prohibition is primarily aimed at preventing idolatry and worship. By using Fazlur Rahman’s perspective, it becomes evident that, within a modern context, painting does not necessarily involve worship and can be accepted as a form of creative expression. This highlights the need to adapt Islamic legal interpretations to social changes while maintaining core religious principles, thereby reducing misunderstandings in the development of contemporary art.